Soy Reduces Bone Turnover Markers in Women During Early Menopause: A Randomized Controlled Trial. (6th September 2016) - Sathyapalan, Thozhukat; Aye, Mo; Rigby, Alan S; Fraser, William D; Thatcher, Natalie J; Kilpatrick, Eric S; Atkin, Stephen L
ABSTRACT: Menopausal estrogen loss leads to an increased bone loss. Soy isoflavones can act as selective estrogen receptor modulators, their role in bone turnover is unclear. The primary outcome was assessing changes in plasma bone turnover markers. The secondary outcomes were assessing changes in cardiovascular risk markers including insulin resistance, blood pressure, and lipid profile. We performed a double‐blind randomized parallel study in which 200 women within 2 years after the onset of their menopause were randomized to 15 g soy protein with 66 mg isoflavone (SPI) or 15 g soy protein alone (SP), daily for 6 months. There was a significant reduction in type I collagen crosslinked beta C‐telopeptide (βCTX) (bone‐resorption marker) with SPI supplementation (0.40 ± 0.17 versus 0.15 ± 0.09 μg/L; p  < 0.01) compared to SP supplementation (0.35 ± 0.12 versus 0.35 ± 0.13 μg/L; p  = 0.92) after 6 months. There was also a significant reduction in type I procollagen‐N‐propeptide (P1NP) (bone formation marker) with SPI supplementation (50.5 ± 25.0 versus 34.3 ± 17.6 μg/L; p  < 0.01), more marked between 3 and 6 months. Following SPI there was a significant reduction in fasting glucose, fasting insulin, insulin resistance, and systolic blood pressure whereas no significant changes in these parameters was observed with SP. There were no significant changes in fasting lipid profile and diastolic blood pressure with either preparation. There was a significant increase in TSH and reduction in free thyroxine ( p  < 0.01) with SPI supplementation though free tri‐iodothyronine was unchanged. In conclusion, soy protein with isoflavones may confer a beneficial effect on bone health, analogous to the mode of action of antiresorptive agents, albeit to a less magnitude. There was a significant improvement of cardiovascular risk markers, but a significant increase in TSH and reduction in free thyroxine after SPI supplementation indicating a detrimental effect on thyroid function. © 2016 American Society for Bone and Mineral Research.